Design Science and Its Importance in the German Mathematics Educational Discussion. ([2016]) - Nührenbörger, Marcus; Roesken, Bettina; Fung, Chun-Ip; Schwarzkopf, Ralph; Wittmann, Erich Christian; Akinwunmi, Kathrin; Lensing, Felix; Schacht, Florian
No abstract available